miR-21-5p Inhibits Ferroptosis in Hepatocellular Carcinoma Cells by Regulating the AKT/mTOR Signaling Pathway through MELK - Zongqiang Hu; Laibang Li; Ma Li; Xibing Zhang; Yu Zhang; Jianghua Ran; Li Li (Journal of Immunology Research)
Background. Hepatocellular carcinoma (HCC) is one of the most prevalent cancers, and its incidence rate is increasing worldwide. At present, there is no ideal treatment for HCC. In recent years, molecular-targeted therapy has shown significant therapeutic benefits for patients. Ferroptosis is a modality of regulated cell death, and previous studies have found that inducing ferroptosis in liver cancer cells can inhibit the progression of liver cancer. The aim of this study is to investigate the regulatory mechanism of miR-21-5p in regulating ferroptosis in HCC cells. Methods. CCK-8 was used to measure cell viability, EdU and colony formation were used to measure cell proliferation, and Transwell assays were used to measure cell migration and invasion. RT-qPCR was used to detect the level of miR-21-5p, Western blotting was used to detect the protein expression level, a dual-luciferase reporter gene assay was used to determine the targeting relationship between miR-21-5p and MELK, and coimmunoprecipitation was used to determine the interaction between MELK and AKT. Results. Overexpression of miR-21-5p and MELK facilitated the viability, proliferation, colony formation, invasion, and migration of HCC cells. Downregulation of miR-21-5p suppressed the level of MELK and the progression of HCC. MELK regulated the AKT/mTOR signaling pathway, causing changes in the levels of GPX4, GSH, FTH1, xCT, heme oxygenase 1(HO-1), reactive oxygen species, and Fe2+ to regulate the ferroptosis of hepatoma cells. Erastin, an inducer of ferroptosis, attenuated the repressive influence of miR-21-5p on ferroptosis in HCC cells. Conclusion. In summary, this study demonstrates that miR-21-5p inhibits the ferroptosis of HCC cells by regulating the AKT/mTOR signaling pathway through MELK.